2004
DOI: 10.1200/jco.2004.08.141
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin for Neuropathic Cancer Pain: A Randomized Controlled Trial From the Gabapentin Cancer Pain Study Group

Abstract: Gabapentin is effective in improving analgesia in patients with neuropathic cancer pain already treated with opioids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
184
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(191 citation statements)
references
References 36 publications
5
184
0
2
Order By: Relevance
“…It is believed that gabapentin acts on the α-2-δ type of Ca 2+ channels. Gabapentin has relieved pain and associated symptoms in patients with both peripheral diabetic neuropathy, post-herpetic neuralgia, HIV-related neuropathy, and cancer-related neuropathic pain [41]- [44]. The dosages used in these studies typically ranged from 900 -3600 mg daily in 3 divided doses.…”
Section: Gabapentinmentioning
confidence: 99%
“…It is believed that gabapentin acts on the α-2-δ type of Ca 2+ channels. Gabapentin has relieved pain and associated symptoms in patients with both peripheral diabetic neuropathy, post-herpetic neuralgia, HIV-related neuropathy, and cancer-related neuropathic pain [41]- [44]. The dosages used in these studies typically ranged from 900 -3600 mg daily in 3 divided doses.…”
Section: Gabapentinmentioning
confidence: 99%
“…An inconvenience with the use of opioids is that this type of drug may be overused, abused or misused in chronic cancer [50]. An anticonvulsant, gabapentin, has been demonstrated to be useful in the treatment of neuropathic cancer pain [51], as well as having adjuvant properties, synergistic with opioid analgesics [52].…”
Section: Other Treatments Of Sres In Patients With Advanced Cancermentioning
confidence: 99%
“…As opposed to non-cancer pain states, few studies have evaluated gabapentin for the treatment of cancer-related pain. These studies showed significant differences in pain intensities, although the clinical meaning remains uncertain [4,34]. There have been no head-to-head studies to directly compare the efficacies of gabapentin and pregabalin.…”
Section: Non-opioid Drugsmentioning
confidence: 99%